Guinea pig infected with Mycobacterium tuberculosis via oral consumption. Issue 1 (1st January 2018) - Gao, Jianfeng; Guo, Ming; Teng, Li; Bao, Rong; Xian, Qiaoyang; Wang, Xin; Ho, Wenzhe
ABSTRACT: Guinea pig represents a highly suitable animal model for study of Mycobacterium tuberculosis ( Mtb )infection, as it demonstrates similarities to Mtb pulmonary infection in humans. It is known that guinea pigs can be efficiently infected by the respiratory or subcutaneous exposure to Mtb . However, information on Mtb infection through oral route is almost absent in the literature. Here, we examined whether guinea pigs can be infected by drinking Mtb containing water. Our findings confirmed that the guinea pigs could be infected with Mtb via drinking virulent water. The infected guinea pigs developed uniform oval-craterform ulcers at the 30th day after infection. Bacterial cultures showed Mtb growth in the lungs and spleens from the guinea pigs infected with high dose of Mtb . In addition, the infected animals had histopathological granulomatous lesions in lungs, spleens and mesenteric lymph nodes. We provide the compelling evidence that the guinea pigs could be infected by drinking Mtb containing water. The clinical and pathological observations in the infected animals were similar to those found in guinea pigs infected via the respiratory or subcutaneous routes.